Anti-Bronchospasmodic Effect of JME-173, a Novel Mexiletine Analog Endowed With Highly Attenuated Anesthetic Activity - Carvalho, Katharinne Ingrid Moraes; Coutinho, Diego de Sá; Joca, Humberto Cavalcante; Miranda, Artur Santos; Cruz, Jader dos Santos; Silva, Emerson Teixeira; Souza, Marcus Vinícius Nora; Faria, Robson Xavier; Silva, Patricia Machado Rodrigues e; Costa, Jorge Carlos Santos; Martins, Marco Aurélio (Frontiers in Pharmacology, 2020)
Local anaesthetics (LAs), such as lidocaine and mexiletine, inhibit bronchoconstriction in asthmatics, but adverse effects limit their use for this specific clinical application. In this study, we describe the anti-spasmodic properties of the mexiletine analogue 2-(2-aminopropoxy)-3,5-dimethyl, 4-Br-benzene (JME-173), which was synthesized and screened for inducing reduced activity on Na+ channels. The effectiveness of JME-173 was assessed using rat tracheal rings, a GH3 cell line and mouse cardiomyocytes to access changes in smooth muscle contraction, and Na+, and Ca++ionic currents, respectively. Bronchospasm and airway hyper-reactivity (AHR) were studied using whole-body barometric plethysmography in A/J mice. We observed that the potency of JME-173 was 653-fold lower than mexiletine in inhibiting Na+ currents, but 12-fold higher in inhibiting L-type Ca++ currents. JME-173 was also more potent than mexiletine in inhibiting tracheal contraction by carbachol, allergen, extracellular Ca++ or sodium orthovanadate provocations. The effect of JME-173 on carbachol-induced tracheal contraction remained unaltered under conditions of de-epithelized rings, β2-receptor blockade or adenylate cyclase inhibition. When orally administered, JME-173 and theophylline inhibited methacholine-induced bronchospasm at time points of 1 h and 3 h post-treatment, while only JME-173 remained active for at least 6 h. In addition, JME-173 also inhibited AHR in a mouse model of lipopolysaccharide (LPS)-induced lung inflammation. Thus, the mexiletine analogue JME-173 shows highly attenuated activity on Na+ channels and optimized anti-spasmodic properties, in a mechanism that is at least in part mediated by regulation of Ca++ inflow towards the cytosol. Thus, JME-173 is a promising alternative for the treatment of clinical conditions marked by life-threatening bronchoconstriction.